Regenerative Therapies in Dry Eye Disease: From Growth Factors to Cell Therapy - Villatoro, Antonio J; Fernández, Viviana; Claros-Gil, Silvia; Alcoholado Cueto, Cristina; Cifuentes-Rueda, Manuel; Merayo-Lloves, Jesús; Andrades-Gómez, José Antonio; Becerra-Ratia, José (MDPI, 2017)
Dry eye syndrome is a complex and insidious pathology with a high level of prevalence among the human population and with a consequently high impact on quality of life and economic cost. Currently, its treatment is symptomatic, mainly based on the control of lubrication and inflammation, with significant limitations. Therefore, the latest research is focused on the development of new biological strategies, with the aim of regenerating affected tissues, or at least restricting the progression of the disease, reducing scar tissue, and maintaining corneal transparency. Therapies range from growth factors and cytokines to the use of different cell sources, in particular mesenchymal stem cells, due to their multipotentiality, trophic, and immunomodulatory properties. We will review the state of the art and the latest advances and results of these promising treatments in this pathology.
Keywords: Células madre; Medicina regenerativa; Mesenchymal stem cells; Allogenic cell therapy; Growth factor; Lacrimal gland; Dry eye; Keratoconjunctivitis sicca; Regenerative medicine